Treatment and Long-Term Outcomes of Primary Central Nervous System Vasculitis: Updated Results From the French Registry. Issue 8 (August 2018) - de Boysson, Hubert; Arquizan, Caroline; Touzé, Emmanuel; Zuber, Mathieu; Boulouis, Grégoire; Naggara, Olivier; Guillevin, Loïc; Aouba, Achille; Pagnoux, Christian
Abstract : Background and Purpose—: We aimed to analyze the long-term outcomes of patients with primary central nervous system vasculitis according to the different therapeutic strategies used to induce remission. Methods—: We assessed the rate of prolonged remission (defined by the absence of relapse at ≥12 months after diagnosis) and the functional status at last follow-up in patients with primary central nervous system vasculitis included in the French cohort, who achieved a first remission according to the 3 main groups of treatments administered: glucocorticoids only (group 1); induction treatment with glucocorticoids and an immunosuppressant, but no maintenance (group 2); and combined treatment with glucocorticoids and an immunosuppressant for induction followed by maintenance therapy (group 3). Good functional status was defined as a modified Rankin Scale score ⩽2 at the last follow-up. Results—: Remission was achieved with the initial induction treatment in 106 (95%) of the 112. Prolonged remission without relapse was observed in 70 (66%) patients after 57 (12–198) months of follow-up. A good functional status at last follow-up (ie, modified Rankin Scale score ⩽2) was observed in 63 (56%) patients. Overall mortality was 8%. The initial severity and the radiological presentations were comparable in the 3 treatment groups. More prolonged remissions ( P =0.003) and a better functional status at the last follow-up ( P =0.0004) were observed in group 3. In multivariate analysis, the use of maintenance therapy was associated with prolonged remission (odds ratio, 4.32 [1.67–12.19]; P =0.002) and better functional status (odds ratio, 8.09 [3.24–22.38]; P <0.0001). Conclusions—: This study suggests that maintenance therapy with an immunosuppressant combined with glucocorticoids lead to the best long-term clinical and functional outcomes in patients with primary central nervous system vasculitis after having achieved remission with either glucocorticoids alone or in combination with another immunosuppressant. Abstract : Supplemental Digital Content is available in the text.